The Influence of Problem-Based Learning (PBL) Models on the Biology Learning Outcomes of High School Students - Kurnianti, Pelasari; Hiola, Siti Fatmah; Bahri, Arsad; Nurhayati B, Nurhayati B; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2024)
Abstract. This research aims to determine the effect of the problem-based learning model on the biology learning outcomes of high school students in the circulatory system topic. This is a quasi-experimental study with a pretest-posttest control group design. The study was conducted at SMA Negeri 9 Makassar. The population in this study comprised all eleventh-grade students of SMA Negeri 9 Makassar. The research sample included class XI Biology 5 as the control class and XI Biology 7 as the experimental class, selected through random sampling. The research instrument consisted of a multiple-choice test with 25 questions. Data analysis techniques used were descriptive statistical analysis and inferential statistical analysis, including normality tests, homogeneity tests, and hypothesis tests in the form of ANCOVA tests. The analysis results showed that the learning outcomes of students in the class taught using the PBL model, with an average pretest score of 31.12, categorized as poor and very poor, significantly improved, marked by an average posttest score of 86, categorized as very good and good. The ANCOVA test results showed a sig. value of < 0.05, indicating that the problem-based learning model has an effect on the biology learning outcomes of high school students.Keyword: learning outcomes, problem-based learning